Measurement of ZZ production in leptonic final states at √s of 1.96 TeV at CDF - Aaltonen, T; Álvarez Gonzlez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
In this Letter, we present a precise measurement of the total ZZ production cross section in pp̄ collisions at √s=1.96TeV, using data collected with the CDF II detector corresponding to an integrated luminosity of approximately 6fb -1. The result is obtained by combining separate measurements in the four-charged ( ′′) and two-charged-lepton and two-neutral-lepton (νν) decay modes of the Z boson pair. The combined measured cross section for pp̄→ZZ is 1.64-0.38+0.44pb. This is the most precise measurement of the ZZ production cross section in 1.96 TeV pp̄ collisions to date. © 2012 American Physical Society.